Women entrepreneurship: Research review and future directions - Vanita Yadav; Jeemol Unni (Journal of Global Entrepreneurship Research, 2016)
Studies on women entrepreneurship have witnessed a rapid growth over the past 30 years. The field is in an adolescence stage with a considerable number of journal articles, literature reviews and books being published on women entrepreneurs. The objective of this study is twofold. First is to examine the number of papers published on women entrepreneurship in 12 established entrepreneurship journals from 1900 to 2016. Second is to assess the growth of the field by specifically reviewing literature reviews published from 1980s till 2016 and put forward future research directions. Our review findings suggest that there is still a long way to go in terms of building a strong theoretical base for research on women entrepreneurship. The lens of feminist theories can be applied in conjunction with the existing entrepreneurship theories to advance the field. Methodologically, past research is dominated by the positivist paradigm and there is a need to embrace innovative methods to build explanations using a constructionist approach. Further, studies are mostly restricted within national boundaries primarily being conducted in developed economies. There is a need to build transnational networks and foster professional communities to enable the growth of the field.
Keywords: 650; Women Entrepreneurship; Gender and Entrepreneurship; Female Entrepreneurship; New Venture Creation; Literature Review